2019
DOI: 10.1038/s41419-019-1826-4
|View full text |Cite
|
Sign up to set email alerts
|

MLP-deficient human pluripotent stem cell derived cardiomyocytes develop hypertrophic cardiomyopathy and heart failure phenotypes due to abnormal calcium handling

Abstract: Muscle LIM protein (MLP, CSRP3 ) is a key regulator of striated muscle function, and its mutations can lead to both hypertrophic cardiomyopathy (HCM) and dilated cardiomyopathy (DCM) in patients. However, due to lack of human models, mechanisms underlining the pathogenesis of MLP defects remain unclear. In this study, we generated a knockout MLP/CSRP3 human embryonic stem cell (hESC) H9 cell line using CRISPR/Cas9 mediated gene disruption. CSRP3 disruption had no i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 51 publications
(66 reference statements)
1
44
0
Order By: Relevance
“…Firstly, maturity is critical for studying the function of hESC-CMs. Genetically modified hPSCs have been commonly used to study the gene function in cardiomyocytes, indicating that these cells are excellent models for cardiovascular research (Lan et al, 2013;Fogarty et al, 2017;Mosqueira et al, 2018;Li et al, 2019). In this study, we found that RRAD −/− cardiomyocytes were more prone to hypertrophic phenotype, whereas, WT cardiomyocytes were also exhibited a certain phenotype such as low frequencies of myofibrillar disarray, multi-nucleation under the same culture conditions.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Firstly, maturity is critical for studying the function of hESC-CMs. Genetically modified hPSCs have been commonly used to study the gene function in cardiomyocytes, indicating that these cells are excellent models for cardiovascular research (Lan et al, 2013;Fogarty et al, 2017;Mosqueira et al, 2018;Li et al, 2019). In this study, we found that RRAD −/− cardiomyocytes were more prone to hypertrophic phenotype, whereas, WT cardiomyocytes were also exhibited a certain phenotype such as low frequencies of myofibrillar disarray, multi-nucleation under the same culture conditions.…”
Section: Discussionmentioning
confidence: 56%
“…Results as shown in Figure 3C, although "circadian entrainment" and "axon guidance" rank first and second in GO analysis of 15 significantly different pathways, they were involved in circadian rhythm control of organism (Golombek and Rosenstein, 2010) and neurological disorders (Van Battum et al, 2015), respectively. We focused on the third "calcium signal pathway" for it is closely related to the physiological function of RRAD gene and it has been confirmed as the central mechanism of cardiac hypertrophy in previous studies (Lan et al, 2013;Dewenter et al, 2017;Li et al, 2019). Taken together, these findings suggested that RAD is involved in the regulation of biological processes and is closely related to the regulation of calcium ion function.…”
Section: Differential Transcriptome Of Rrad −/− Cardiomyocytesmentioning
confidence: 82%
See 3 more Smart Citations